2019
DOI: 10.5194/bg-16-2733-2019
|View full text |Cite
|
Sign up to set email alerts
|

Composition and cycling of dissolved organic matter from tropical peatlands of coastal Sarawak, Borneo, revealed by fluorescence spectroscopy and parallel factor analysis

Abstract: Abstract. Southeast Asian peatlands supply ∼10 % of the global flux of dissolved organic carbon (DOC) from land to the ocean, but the biogeochemical cycling of this peat-derived DOC in coastal environments is still poorly understood. Here, we use fluorescence spectroscopy and parallel factor (PARAFAC) analysis to distinguish different fractions of dissolved organic matter (DOM) in peat-draining rivers, estuaries and coastal waters of Sarawak, Borneo. The terrigenous fractions showed high concentrations at fres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 96 publications
6
49
0
Order By: Relevance
“…This finding may be related to the flocculation of the negatively charged colloids with cations during the mixing of fresh-saline water. This phenomenon has been observed in many rivers and simulation experiments (Boyle et al, 1977;Oldham et al, 2017;Zhu et al, 2018). In addition, dFe was negatively correlated with SPM in low-salinity waters ( Fig.…”
Section: Seasonal and Spatial Variation In Dfe In The Rajang Estuarysupporting
confidence: 71%
See 3 more Smart Citations
“…This finding may be related to the flocculation of the negatively charged colloids with cations during the mixing of fresh-saline water. This phenomenon has been observed in many rivers and simulation experiments (Boyle et al, 1977;Oldham et al, 2017;Zhu et al, 2018). In addition, dFe was negatively correlated with SPM in low-salinity waters ( Fig.…”
Section: Seasonal and Spatial Variation In Dfe In The Rajang Estuarysupporting
confidence: 71%
“…It has been confirmed that the partition coefficient of dFe decreases with increasing SPM concentration and is inversely proportional to the log of the SPM concentration, termed the particle concentration effect (Benoit, 1995;Jiann et al, 2013;Turner and Millward, 2002). Furthermore, Zhu et al (2018) suggested that desorption from particles was the main reason for the dFe enhancement occurring in the river mouth area of the Changjiang estuary. In the wet season, Serendeng tributary samples were collected during a spring tide.…”
Section: Seasonal and Spatial Variation In Dfe In The Rajang Estuarymentioning
confidence: 92%
See 2 more Smart Citations
“…In the Maludam Estuary, DOSe concentrations were negatively correlated with the CDOM spectral slope from 275 to 295 nm (S 275-295 ) and were positively correlated with the humic-like C3 component and specific UV absorbance at 254 nm (SUVA 254 ) during estuarine mixing in both seasons (data from Martin et al, 2018;Zhou et al, 2019, Fig. 5a-c).…”
Section: Correlation Between Se Species With Do Ph and Dissolved Orgmentioning
confidence: 99%